The elastic, electron, phonon, and vibrational properties of monolayer XO2 (X = Cr, Mo, W) from first principles calculations. (March 2022) - Fang, Wenyu; Xiao, Xinglin; Wei, Haoran; Chen, Yue; Li, Mingkai; He, Yunbin
Abstract: While transition metal oxides (TMO) with two-dimensional (2D) structure have attracted much attention, TMO (group P-6 m2) composed of VIB group elements have rarely been reported. In this work, we propose three kinds of monolayer 2D oxides, namely CrO2, MoO2, and WO2, and have further investigated their stability, elastic, electron, phonon, and thermal properties by density functional theory (DFT) calculations. The results show that all the monolayer oxides XO2 (X = Cr, Mo, W) have high mechanical and dynamic stability, and their Young's moduli/Poisson ratios are respectively 235.84 N·m −1 /0.33, 237.01 N·m −1 /0.36, and 268.51 N·m −1 /0.33 with high isotropy. In addition, they are all semiconductors with indirect band gaps of 1.08 eV, 1.52 eV, and 2.01 eV, respectively. Based on the deformation potential theory, we found that the carrier mobilities of monolayer XO2 exhibit certain anisotropy, and the electron/hole mobilities are as high as 415.28/779.15 cm 2 ·V −1 ·s −1, 989.06/684.67 cm 2 ·V −1 ·s −1, and 1163.53/576.09 cm 2 ·V −1 ·s −1, respectively. Also, due to the high group velocities and phonon lifetimes, they exhibit high lattice thermal conductivities, up to 78.23 Wm −1 K −1, 81.44 Wm −1 K −1, and 39.43 Wm −1 K −1 at room temperature. All these properties indicate that monolayer XO2 have potential applications in optoelectronic devices and thermal conductive components in the future. Highlights: Monolayer XO2 (XCr, Mo, W) semiconductors have indirect band gaps of 1.08, 1.52, and 2.01 eV, respectively. They all have high carrier mobilities (10 2 ~10 3 cm 2 ·V −1 ·s −1 ) for both electrons and holes. They exhibit high lattice thermal conductivities up to 78.23, 81.44, and 39.43 Wm −1 K −1, respectively, at 300 K.